Acute inflammatory profile of patients submitted to pulmonary resection - Andrea Pelicia Roso de Souza; Raquel Palhares; Letícia Baltieri; Ricardo Kalaf Mussi; Edson Antunes; Glaucia Coelho de Mello (Acta Cirúrgica Brasileira)
ABSTRACT Purpose: To establish a profile of the inflammatory response in the preoperative and postoperative period of pulmonary resection of patients without postoperative complications, in order to trace the inflammatory profile of lung resection surgery. Methods: Six collections of arterial and venous blood were performed for data analysis, one sample in the preoperative, immediate postoperative, 4, 8, 24, and 48 hours after surgery. Twenty-seven patients with a median age of 63 years old, ranging from 29 to 80 years old, were included. Results: The leukocyte count showed a significant increase in the times: immediate postoperative and 4 hours after surgery, in relation to the preoperative period. Concomitantly, there was an increase in lactate, heart rate, interleukin (IL)-6 and IL-8 after 4 hours of surgery. The platelet count showed a significant decrease in 48 h, associated with an increase in IL-1β and tumor necrosis factor-α. A significant increase in IL-10 was observed in the immediate postoperative. Conclusion: The study may contribute to the search for more specific and adequate alternatives for controlling the inflammatory response. In this way, the intervention would be specific to that cytokine that causes the greatest harm to the patient, as well as to the moment of the intervention.